Marketing Mix’s of Bubble Tea Consumers in the Digital Era - Sangprong, Sagultip (Chophayom Journal, 2025)
This academic article finds that the marketing mix is a fundamental element in conducting business, whether it is a product-based or service-based business. It is essential to apply marketing mix strategies in business operations. Bubble tea is one of the most consumed beverages among Thai consumers. Its modern packaging and affordable price meet the needs of the target group and have become key selling points. In the digital age, Generation Z is considered the primary target of marketing. This group has high purchasing power, creative thinking, and tends to search for product information, read reviews regarding prices and quality before making purchasing decisions. The objective of this study is to synthesize the components of the marketing mix by reviewing academic articles and research studies. The results reveal that the components of the marketing mix include: Product, Price, Place (distribution channels), Promotion, People, Process, and Physical evidence. Additionally, the components of the consumer decision-making process include: Need recognition, Information search, Evaluation of alternatives, Purchase decision, and Post-purchase behavior. Each factor plays an important role in the interconnection of business operations and serves as a marketing tool to enhance the efficiency of product or service businesses.